TEACHING VOCABULARY USING FLASHCARD TO YOUNG LEARNER - Siti Ngarofah; Ani Sumarni (PROJECT (Professional Journal of English Education), 2018)
This research entitled “ teaching vocabulary using flashcard to young learners” is a study to investigate the influence of using flashcard in teaching vocabulary to students of grade four in elementary school. This study was done using pre-experimental research. There are three steps in doing research design. First, the writer gave pretest to the students of elementary school grade two as the dependent variable. Second, the writer implicate the treatment to the subjects by teaching vocabulary using flashcard. Final steps, the writer gave subjects posttest. The results of the research showed that there is an improvement in student’s vocabulary mastery after the students were thought vocabulary mastery using flashcard. The students of elementary school grade two could memorize and understand easily and they were encouraged to learn English. Thus, the researcher could conclude that using flashcard in teaching vocabulary to the students grade two is recommended as teaching program to learn English.Keywords: teaching vocabulary, flashcard, young learner.